Transition from the industrial clusters to the smart specialization: a case study - Yelena Petrenko; Elena Vechkinzova; Viktor Antonov (Insights into Regional Development)
Kazakhstan faced the problem of falling industrial production and decrease in efficiency of former managerial methods of territorial development. Transition to the new Smart Specialization approach provides better understanding of the specifics of the region and provides the highest return on investment in innovation. The authors produce rationale for the selection of regions of Kazakhstan to determine their smart specialization. There were determined the regions, in which it is advisable to develop the general purpose technologies, and the territories, where it is more profitable to focus on applied research and transmitting them into practice in relation to existing products and technological processes.